Influenza M2 protein regulates MAVS-mediated signaling pathway through interacting with MAVS and increasing ROS production. Issue 7 (3rd July 2019) - Wang, Ruifang; Zhu, Yinxing; Lin, Xian; Ren, Chenwei; Zhao, Jiachang; Wang, Fangfang; Gao, Xiaochen; Xiao, Rong; Zhao, Lianzhong; Chen, Huanchun; Jin, Meilin; Ma, Wenjun; et al.
ABSTRACT: Influenza A virus can evade host innate immune response that is involved in several viral proteins with complicated mechanisms. To date, how influenza A M2 protein modulates the host innate immunity remains unclear. Herein, we showed that M2 protein colocalized and interacted with MAVS (mitochondrial antiviral signaling protein) on mitochondria, and positively regulated MAVS-mediated innate immunity. Further studies revealed that M2 induced reactive oxygen species (ROS) production that was required for activation of macroautophagy/autophagy and enhancement of MAVS signaling pathway. Importantly, the proton channel activity of M2 protein was demonstrated to be essential for ROS production and antagonizing the autophagy pathway to control MAVS aggregation, thereby enhancing MAVS signal activity. In conclusion, our studies provided novel insights into mechanisms of M2 protein in modulating host antiviral immunity and uncovered a new mechanism into biology and pathogenicity of influenza A virus. Abbreviations : AKT/PKB: AKT serine/threonine kinase; Apo: apocynin; ATG5: autophagy related 5; BAPTA-AM: 1, 2-Bis(2-aminophenoxy) ethane- N, N, N′, N′ -tetraacetic acid tetrakis; BECN1: beclin 1; CARD: caspase recruitment domain; CCCP: carbonyl cyanide m-chlorophenylhydrazone; CQ: chloroquine; DCF: dichlorodihyd-rofluorescein; DPI: diphenyleneiodonium; DDX58: DExD/H-box helicase 58; eGFP: enhanced green fluorescent protein; EGTA: ethylene glycol-bis(2-aminoethylether)- N, N, N′, N′ -tetraacetic acid; ER: endoplasmic reticulum; hpi: hours post infection; IAV: influenza A virus; IFN: interferon; IP: immunoprecipitation; IRF3: interferon regulatory factor 3; ISRE: IFN-stimulated response elements; LIR: LC3-interacting region; MAP1LC3B/LC3B: microtubule associated protein 1 light chain 3 beta; MAVS: mitochondrial antiviral signaling protein; MMP: mitochondrial membrane potential; MOI, multiplicity of infection; mRFP: monomeric red fluorescent protein; MTOR: mechanistic target of rapamycin kinase; NC: negative control; NFKB/NF-κB: nuclear factor kappa B; PI3K: class I phosphoinositide 3-kinase; RLR: RIG-I-like-receptor; ROS: reactive oxygen species; SEV: sendai virus; TM: transmembrane; TMRM: tetramethylrhodamine methylester; VSV: vesicular stomatitis virus